First-generation college students’ hope for change through counseling: a comparative study - Theodore T. Bartholomew; Candace Tsai; Lizbeth Valdivia-Jauregui; Alondra Alvarez Murillo; Angela Molina; Alejandro Morales (Cogent Mental Health)
First-generation college students in United States postsecondary education institutions is a growing population. Scholars have shown areas of increased distress amongst first-generation college students and a concordant lower likelihood of using psychological services on campuses. These differences are contextualized in barriers that first-generation college students endure: a lack of familiarity with educational institutions, hindered belongingness, financial difficulties, and others. Missing in the literature, however, is more attention to why first-generation college students may underutilize services compared to continuing-generation college students. One such reason may revolve around hope for counseling. We collected data about attitudes towards help-seeking, stigmatization of help-seeking, hope for counseling, and psychological stress from 518 (312 first- generation college students) participants from two higher education contexts. Results showed no significant difference in hope for counseling, stigma of help-seeking, or attitudes about help-seeking between first- and continuing-generation college students; however, first-generation college students did report less current counseling service utilization. Findings are discussed regarding support for first-generation college students.